The Q336H MAPT Mutation Linked to Pick’s Disease Leads to Increased Binding of Tau to the Microtubule Network via Altered Conformational and Phosphorylation Effects - Siano, Giacomo; Micaelli, Mariachiara; Scarlatti, Arianna; Quercioli, Valentina; Di Primio, Cristina; Cattaneo, Antonino (Frontiers in Molecular Neuroscience, 2020)
Tauopathies are neurodegenerative disorders characterized by Tau aggregation. Genetic studies on familial cases allowed for the discovery of mutations in the MAPT gene that increase Tau propensity to detach from microtubules and to form insoluble cytoplasmic Tau aggregates. Recently, the rare mutation Q336H has been identified to be associated to Pick’s disease and biochemical analyses demonstrated its ability to increase the MTs polymerization, thus revealing an opposite character compared to other Tau mutations studied so far. Here we investigated the biophysical and molecular properties of TauQ336H in living cells by the employment of the conformational Tau biosensor CST. We found that this mutation alters Tau conformation on microtubules, stabilizes its binding to tubulin and is associated with a paradoxical lower level of Tau phosphorylation. Moreover, we found that this mutation impacts on the cytoskeletal complexity by increasing the tubulin filament length and the number of branches. However, despite these apparently non-pathological traits, we observed the formation of intracellular inclusions confirming that Q336H leads to aggregation. Our results suggest that the Tau aggregation process might be triggered by molecular mechanisms other than Tau destabilization or post-translational modifications which are likely to be detrimental to neuronal function in vivo.